Finding a good starting place: An interview with scholars in the CLEAR Lab. Issue 2 (15th March 2022) - Yanchapaxi, María Fernanda; Liboiron, Max; Crocker, Katherine; Smiles, Deondre; Tuck, Eve
Abstract: The CLEAR lab is an interdisciplinary plastic pollution laboratory whose methods foreground humility and good land relations. In this interview, María Fernanda Yanchapaxi and Eve Tuck speak with CLEAR lab founder, Max Liboiron, and co-investigators, Katherine Crocker and Deondre Smiles. Together, they explore Indigenous perspectives on climate change and outline the problems with how Western education thinks about it. Our guests question individualism in the understandings of and responses to climate change and reveal the importance of dismantling individual saviour complex perspectives embedded in educational approaches. Our guests invite educators to reflect on and redefine the values at the core of their practice and seek new ways to act on them.